A low-cost ChArUco-based 3D scanner for cultural heritage. Issue 1 (November 2020) - Puggelli, Luca; Furferi, Rocco; Volpe, Yary; Governi, Lapo
Abstract: In the region of the cultural patrimony, operators use high-resolution orthophotos of paintings for the restoration, monitoring and electronic recording and exhibition purposes. Unfortunately, artworks that are to be restored and/or shown in digital museums are painted on canvas that are far from perfectly planar. Professional documents surrounding an artwork to be preserved in digital collections or museums can therefore be enhanced with information relating to the paintings' 3D structure. This paper proposes both the design of a portable low-cost device that enables the acquisition of 3D geometry of painting and the procedure for triangulation of 3D data. This process uses a set of fiducial markers to set and continuously control the mutual orientation of the laser source and the camera and works accordingly to the principle of laser-camera triangulation.